TIKTOK AS A SUPPLEMENTARY MEDIUM IN EDUCATIONAL CONTEXTS: AFFORDANCES, LIMITATIONS, AND PEDAGOGICAL IMPLICATIONS - khairunnisa fersya (CV Grasta Glory, 2026)
Assimilations Here, the present research looks into the relevance of the TikTok application as a short video delivery platform in the context of educational delivery. This investigation uses a systematic literature review and is qualitative in nature aimed at examining the role of app specific features in informal learning through TikTok app short video content, algorithm-driven personalization, social media as they control the informal learning process. In general, the investigation has implications for the TikTok app as a useful educational tool that makes the educational material more widely accessible, promotes learners’ independence and motivates users through entertaining contents, it even serves as an educational resource when aimed at the youth demographic and its tendency toward fast communication. But, the application of the TikTok app carries with it a host of disadvantages: wrong information sent through the application, the lack of in-depth information, as well as inherent distractibility. Compared to more similar kinds of services, such as Google Classroom and YouTube, this analysis demonstrates that